Mothers’ knowledge and attitudes regarding child feeding recommendations, complementary feeding practices and determinants of adequate diet - Kingsley Appiah Bimpong; Ernest Kaa-Emabong Cheyuo; Alhassan Abdul-Mumin; Martin A. Ayanore; Clement K. Kubuga; Victor Mogre (BMC Nutrition, 2020)
Abstract Background Complementary feeding is critical for optimal nutrition in infants and young children as it ensures their growth, health and development to attain their full potential. However, evidence shows that children from developing countries do not meet the core indicators for appropriate complementary feeding. We evaluated mothers’ knowledge and attitudes regarding child feeding recommendations and the determinants of adequate diet among children aged 6–23 months. Methods This cross-sectional study included 200 children aged 6–23 months and their mothers/care givers recruited during child welfare clinics of two health facilities in Ghana. Data was collected using a structured questionnaire. Multivariate logistic regression was used to assess determinants of adequate diet. Results Sixty-eight percent of the mothers knew the recommended duration of continued breastfeeding, 56.5% how to ensure dietary diversity and enrich their children’s diets and 94% (n = 188) had positive attitude towards recommended infant and young child feeding practices. Majority of the mothers (92%, n = 183) practiced continued breastfeeding, 10.5% of the children met minimum diet diversity score, 39.5% minimum meal frequency and 8.5% received minimum adequate diet. Determinants of receipt of minimum adequate diet were: having high knowledge in child feeding recommendations (100% vs. 0.0, p < 0.001) and child’s father reportedly earning adequate income to cater for the family (AOR = 12.1 (1.32–109.72, p = 0.027). Conclusion Motherss knowledge levels regarding infant and young child feeding recommendations had notable deficiencies although they generally had a positive attitude towards child feeding recommendations. Knowledge regarding infant and young child feeding recommendations as well as the child’s father having adequate income were important determinants of adequate diet. Nutrition education should emphasize on improving mothers’ nutrition knowledge regarding infant and young child feeding recommendations and supporting mothers to overcome barriers to feed their children with adequate diets.